Effect of continuous chelation on the dentinal tubule penetration of a calcium silicate-based root canal sealer: a confocal laser microscopy study - Reham Hassan; Nehal Nabil Roshdy (BMC, 2023)
Abstract Background This study aimed to evaluate the effect of various irrigation protocols on the penetration depth of a calcium silicate-based sealer into dentinal tubules using confocal laser scanning microscopy (CLSM). Methods Twenty single-rooted mandibular premolars were endodontically prepared and divided into the following two groups according to the irrigation protocol used (n = 10): Group I: NaOCl + EDTA and Group II: continuous chelation (NaOCl/Dual Rinse). Obturation was performed with the warm vertical compaction technique using TotalFill HiFlow bioceramic sealer mixed with a fluorophore dye. Samples were observed using CLSM at 10× to measure the percentage of sealer penetration and its maximum depth into the dentinal tubules. Data were analysed using one-way ANOVA followed by Tukey's post-hoc test. The significance level was set at p < 0.05 within all tests. Results Comparing the overall results of all sections tested, no statistically significant differences existed between the groups regarding the percentage of sealer penetration (p = 0.612) and maximum depth of penetration (p > 0.05). Conclusions With both types of irrigation used, dentinal tubule penetration was higher in the coronal section than in the apical section. Continuous chelation using NaOCl/Dual Rinse HEDP performed better in the coronal segments, while irrigation using NaOCl + EDTA promoted a higher percentage of sealer penetration in the apical segment.